The Republic of the Refugees: Early Modern Migrations and the Dutch Experience - Janssen, Geert H. (The historical journal, 2017)
This essay surveys the wave of new literature on early modern migration and assesses its impact on the Dutch golden age. From the late sixteenth century, the Netherlands developed into an international hub of religious refugees, displaced minorities, and labour migrants. While migration to the Dutch Republic has often been studied in socio-economic terms, recent historiography has turned the focus of attention to its many cultural resonances. More specifically, it has been noted that the arrival of thousands of newcomers generated the construction of new patriotic narratives and cultural codes in Dutch society. The experience of civil war and forced migration during the Dutch revolt had already fostered the development of a national discourse that framed religious exile as a heroic experience. In the seventeenth century, the accommodation of persecuted minorities could therefore be presented as something typically ‘Dutch’. It followed that diaspora identities and signs of transnational religious solidarity developed into markers of social respectability and tools of cultural integration. The notion of a ‘republic of the refugees’ had profound international implications, too, because it shaped and justified Dutch interventions abroad.